Mental health burden of conflict: rates and correlates of depressive and anxiety symptoms among displaced Palestinian children and adolescents in Qatar - Mohamed Adil Shah Khoodoruth (14589828) (2025)
Aims To estimate the prevalence of clinically significant anxiety and depressive symptoms and to identify psychosocial and trauma-related factors associated with symptom severity in this population. Method A cross-sectional study was conducted among 350 Palestinian children (aged 8–17 years) residing in a residential compound in Qatar. Symptoms of anxiety and depression were measured using the Screen for Child Anxiety Related Emotional Disorders-Child Version and the Short Mood and Feelings Questionnaire-Child Version, respectively. A Resilience and Demographic Questionnaire was devised to assess trauma exposure and psychosocial variables. Multiple linear regression identified factors associated with symptom severity. Results Clinically significant anxiety and depressive symptoms were found in 70.9 and 46.0% of participants, respectively. Separation anxiety was the most common subtype. Female gender, witnessing death, physical injury and disrupted caregiving were significantly associated with worse outcomes. Conclusions This study highlights the urgent need for trauma-informed, culturally sensitive mental health services for displaced Palestinian children and young people. While clinical interventions are vital, a sustainable resolution to the conflict is essential to mitigate further psychological harm. Other Information Published in: BJPsych Open License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1192/bjo.2025.10912